2020
DOI: 10.1155/2020/1647617
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis in the Uninjured Limb in Patients with Lower Extremity Fractures: A Retrospective Study

Abstract: Objective. This study is aimed at investigating the incidence of deep vein thrombosis (DVT) in the uninjured limb during hospitalization and 1 month after surgery in patients with lower extremity fractures. Methods. We collected the clinical data of patients with lower extremity fractures in Xi’an Honghui Hospital. Doppler ultrasonography was used to diagnose DVT. According to the results of ultrasonography, the patients were divided into two groups: uninjured limb with DVT group and uninjured limb without DVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The use of DUS, compared to the use of computed tomography (CT) or magnetic resonance imaging (MRI) venography for the detection of DVTs, may partly explain the relatively large gap in incidence rates. We also found that DVTs occurred not only in the injured extremity but also in the non-injured extremity, which is consistent with the findings of Wang et al [ 20 ] This is due to the hypercoagulable state of blood after fracture and the patient's long-term lack of exercise in bed, which leads to not only the affected limb prone to thrombosis, but also the healthy limb prone to thrombosis. This suggests the equal importance of screening for DVT in both the non-injured and injured extremities.…”
Section: Discussionsupporting
confidence: 92%
“…The use of DUS, compared to the use of computed tomography (CT) or magnetic resonance imaging (MRI) venography for the detection of DVTs, may partly explain the relatively large gap in incidence rates. We also found that DVTs occurred not only in the injured extremity but also in the non-injured extremity, which is consistent with the findings of Wang et al [ 20 ] This is due to the hypercoagulable state of blood after fracture and the patient's long-term lack of exercise in bed, which leads to not only the affected limb prone to thrombosis, but also the healthy limb prone to thrombosis. This suggests the equal importance of screening for DVT in both the non-injured and injured extremities.…”
Section: Discussionsupporting
confidence: 92%
“…The use of DUS, compared to the use of computed tomography (CT) or magnetic resonance imaging (MRI) venography for the detection of DVT may be partly explained by the relatively large gap in incidence rates. We also found that DVT occurred not only in the injured extremity but also in the non-injured extremity, which is consistent with the ndings of Wang et al [19]. This suggests the equal importance of screening for DVT in both the non-injured and injured extremities.…”
Section: Discussionsupporting
confidence: 92%
“…DVT refers to thrombosis of the venous lumen after blood clotting abnormally in deep veins, causing venous reflux disorder, limb swelling, and pain [ 1 ]. DVT is a common complication of orthopaedic trauma patients and can lead to chronic pain, secondary varicose veins, ulcers and other serious effects on patients' quality of life [ 2 ]. Distal venous thrombosis without effective anticoagulant treatment could develop into proximal venous thrombosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the fracture, the blood is in a hypercoagulable state, and the surgery is the main treatment for hip fracture. Trauma, limb fixation, surgery and other factors will increase the risk of DVT, so early preventive measures should be taken [ 2 ]. Zhao et al [ 5 ] found that patients with hip fractures should take medication to prevent DVT.…”
Section: Introductionmentioning
confidence: 99%